(v-8)(v+8)=

Simple and best practice solution for (v-8)(v+8)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (v-8)(v+8)= equation:


Simplifying
(v + -8)(v + 8) = 0

Reorder the terms:
(-8 + v)(v + 8) = 0

Reorder the terms:
(-8 + v)(8 + v) = 0

Multiply (-8 + v) * (8 + v)
(-8(8 + v) + v(8 + v)) = 0
((8 * -8 + v * -8) + v(8 + v)) = 0
((-64 + -8v) + v(8 + v)) = 0
(-64 + -8v + (8 * v + v * v)) = 0
(-64 + -8v + (8v + v2)) = 0

Combine like terms: -8v + 8v = 0
(-64 + 0 + v2) = 0
(-64 + v2) = 0

Solving
-64 + v2 = 0

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '64' to each side of the equation.
-64 + 64 + v2 = 0 + 64

Combine like terms: -64 + 64 = 0
0 + v2 = 0 + 64
v2 = 0 + 64

Combine like terms: 0 + 64 = 64
v2 = 64

Simplifying
v2 = 64

Take the square root of each side:
v = {-8, 8}

See similar equations:

| -5x^3+7x^2-5x-1= | | 3m-16-7m=-68 | | 0.8k+7=-0.7k | | 4x^2+5x+5=0 | | Y=0.10x+12 | | 5t+1= | | x*x-11x+19=-5 | | 8x+7=-7k+1 | | x+84=3 | | 17k+11-3k=214 | | j/5+6=66 | | -3[x-1]+8[x-3]=6x+7-5x | | 4t-5= | | 8x^3+3x^3+5= | | y=-5/4+10 | | 5(2-4X)=-20 | | x/10-6=-7 | | 0.3(1+a)=2.1 | | 12-(10n)=-28 | | 19h-12=197 | | -117+64= | | -112=-7m | | 5-7m+9m=9 | | -3=-6/5(1)+b | | 2x^7=7x | | 4y(y+7)=42 | | 0.3(1+a)=2.1a | | 16/9x=128 | | p(x)=x^5-7x^4-2x^3+78x^2-63x-135 | | 6=(7-2x)(3-2x) | | x^2+5=16 | | 4[-8x+5]=-32x-26 |

Equations solver categories